1975
DOI: 10.1038/bjc.1975.62
|View full text |Cite
|
Sign up to set email alerts
|

Pre-natal irradiation and childhood malignancy: a review of British data from the Oxford Survey

Abstract: Summary.-This paper reviews data relating to obstetric radiography from the Oxford Survey of Childhood Cancers, i.e. for deaths in Britain from 1953 to 1967.Some 8513 cases were traced and used in the analyses, together with an equal number of matched controls. The relative risk estimate (1.47 overall) does not vary significantly between different tumour groups, for different ages at death, nor between sexes. Other epidemiological factors-sibship position, maternal age, social class, region of residence and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(132 citation statements)
references
References 14 publications
5
127
0
Order By: Relevance
“…No male excess has been reported in association with in utero diagnostic radiation exposure in two of the largest studies: the Oxford Survey of Childhood Cancers (Bithell and Stewart, 1975) and the North-eastern United States study (Monson and MacMahon, 1984), or in the offspring of atomic bomb survivors who were exposed while in utero (Delongchamp et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…No male excess has been reported in association with in utero diagnostic radiation exposure in two of the largest studies: the Oxford Survey of Childhood Cancers (Bithell and Stewart, 1975) and the North-eastern United States study (Monson and MacMahon, 1984), or in the offspring of atomic bomb survivors who were exposed while in utero (Delongchamp et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Miller (1971) andDraper et al (1977) have shown that the number of families in which two children are affected is too great to be accounted for by chance, and from the latter paper it appears that the excess cannot obviously be explained by association with known genetic disease. The only welldocumented causes of childhood cancer are ionising radiation (particularly antenatal X-rays; see, for example, Bithell and Stewart, 1975) (Knudson, 1978). Draper et al (1992) estimated the risk of retinoblastoma in sibs of affected patients.…”
Section: Methodsmentioning
confidence: 99%
“…This hypothesis was based on the findings of a case -control study which showed that almost twice as many mothers of children who died from leukaemia or malignant disease before the age of 10 had undergone X-ray examinations of the abdomen during pregnancy (pelvimetry) in comparison with mothers of controls (Stewart et al, 1956). Later analyses showed that this excess risk was inversely related to foetal Revised 10 February 2009; accepted 27 February 2009 age and increased with the number of films taken (Bithell and Stewart, 1975). …”
Section: Childhood Exposure To Irmentioning
confidence: 99%